2009
DOI: 10.1021/jp908970f
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Canonical Molecular Orbitals to Identify Fermi Contact Coupling Pathways. 1. Through-Space Transmission by Overlap of 31P Lone Pairs

Abstract: In this work, a new approach to studying coupling pathways for the Fermi contact term of NMR spin-spin coupling constants (SSCCs) is presented. It is based on the known form of propagating the Fermi hole through a canonical molecular orbital (CMO). It requires having an adequate spatial description of the relevant canonical molecular orbitals, which are obtained by expanding CMOs in terms of natural bond orbitals (NBOs). For detecting the relevant contributions of CMOs to a given Fermi contact (FC) pathway, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 50 publications
2
28
0
1
Order By: Relevance
“…The FC term of NMR spin-spin coupling constants is also computed based on the known form of propagation of the Fermi hole through a canonical molecular orbital (CMO). [100] It is also reported that n J XH computed for unsaturated nitriles using B3LYP/ILGO-11//B3LYP is in perfect agreement with the measured values. [101] …”
Section: Computation Of Long-range J-couplingssupporting
confidence: 63%
“…The FC term of NMR spin-spin coupling constants is also computed based on the known form of propagation of the Fermi hole through a canonical molecular orbital (CMO). [100] It is also reported that n J XH computed for unsaturated nitriles using B3LYP/ILGO-11//B3LYP is in perfect agreement with the measured values. [101] …”
Section: Computation Of Long-range J-couplingssupporting
confidence: 63%
“…Recently, a new approach to study coupling pathways for the FC term of SSCCs, was presented and it was dubbed FCCP-CMO [24,25] , which stands for FC coupling pathways studied using canonical molecular orbitals. The corresponding analysis is based on the polarization propagator (PP) expression for the FC term, Eqns (1-3) [26][27][28][29] Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a new approach to study coupling pathways for the FC term of SSCCs, was presented and it was dubbed FCCP‐CMO , which stands for FC coupling pathways studied using canonical molecular orbitals. The corresponding analysis is based on the polarization propagator (PP) expression for the FC term, Eqns (1–3) JFHFC4=ΩFCia,jbJia,jbFC4(FH)where each term in this sum can be expressed as J4ia,jbFC(FH)=Wia,jb3[Uia,HFCUjb,FFC+Uia,FFCUjb,HFC]and Wia,jb3=()A3+B3ia,jb1 are the elements of the inverse of the triplet PP matrix, and matrices 3 A and 3 B can be written in terms of bielectronic molecular integrals.…”
Section: Resultsmentioning
confidence: 99%
“…This is the case of the Lazzeretti et al 's22 approach and of the coupling energy density (CED) approach developed by Malkina and Malkin 23. Recently, a different and very simple approach was presented, which can be used by any NMR laboratory with access to the following common Quantum Chemistry software; the Gaussian 03 package16 of programs and the NBO 5.0 program developed by Weinhold et al 14 This approach24 was dubbed FCCP–CMOs (the study of FC coupling pathways by analyzing CMOs). This analysis is applied in this work to study how the FC term of 2 J C 2 H 3 and 2 J C 3 H 2 SSCCs is transmitted in series 1 and 2 .…”
Section: Fc Term For Ssccmentioning
confidence: 99%
“…A description of the FCCP–CMO analysis and how to properly carry out the analysis of results from calculations can be found in Ref. 24.…”
Section: Fc Term For Ssccmentioning
confidence: 99%